2010
DOI: 10.1007/s12522-010-0064-3
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of ectopic ovary and one case of potential ectopic ovary

Abstract: Ectopic ovary is a rare gynecologic entity. A variety of synonymous terms such as ectopic ovary, supernumerary ovary, accessory ovary, and autoamputation of the ovary have been used to describe this condition. The etiology for ectopic ovary has not been elucidated, but several mechanisms have been proposed. They are categorized as either congenital (embryologically derived) or acquired. This report presents two cases of ectopic ovary resulting from different causes and one case of potential ectopic ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The histogenesis of extraovarian SCST has been a topic of discussion in the literature, and it is speculated that extraovarian SCST originates from postsurgical implants, postinflammatory implants, an accessory ovary, a supernumerary ovary, or ovary autoamputation. 11,34-36 An accessory ovary is excess ovarian tissue that is situated near the normally placed ovary. A supernumerary ovary is ovarian tissue that separates from the normally placed ovary.…”
Section: Discussionmentioning
confidence: 99%
“…The histogenesis of extraovarian SCST has been a topic of discussion in the literature, and it is speculated that extraovarian SCST originates from postsurgical implants, postinflammatory implants, an accessory ovary, a supernumerary ovary, or ovary autoamputation. 11,34-36 An accessory ovary is excess ovarian tissue that is situated near the normally placed ovary. A supernumerary ovary is ovarian tissue that separates from the normally placed ovary.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of an abnormally located ovary is known to be associated with other congenital malformations, mainly pelvic and renal, in up to 36% of cases. 1 Different types of tumors have been reported in ectopic ovarian tissue such as cystadenomas, 4 benign teratomas, 5,6 Brenner's tumors, 7 and fibromas with Meig's syndrome. 8 There have also been cases reported in which an ovary with a benign teratoma had auto-amputated and transplanted in an indirect inguinal hernia 6 and in the recto-uterine cul-de-sac, rectosigmoid colon mucosa 9 secondary to torsion.…”
Section: Ectopic Ovarian Leiomyoma 223mentioning
confidence: 99%
“…[ 1 ] defined the supernumerary ovary as entirely separated from the normal ovary, and is located at a different position, whereas the accessory ovary is defined as excess ovarian tissue that is situated near the normal ovary, which may or may not connect to it. [ 2 3 ]…”
mentioning
confidence: 99%
“…reported that the supernumerary and accessory ovaries are rare conditions that occur in 1 in 29,000 and 1 in 700,000 gynecologic hospital admissions. [ 3 ]…”
mentioning
confidence: 99%